Peran Aktivisme sebagai Mediator dalam Hubungan Social Dominance Orientation terhadap Niat Radikalisme Mahasiswa - Andayu Dyah Fitriannisa; Miftahun Najah (Universitas Muhammadiyah Metro, 2026)
University students are widely regarded as agents of change with highly critical attitudes. However, they are often vulnerable to exposure to radical ideologies. The phenomenon of radicalism in campus environments is a complex issue that can be influenced by how individuals or groups perceive social hierarchies and their participation in social movements. This study aims to examine the effect of Social Dominance Orientation (SDO) on students' tendency toward radicalism, with activism serving as a mediating variable. The study employed a quantitative approach involving 246 student participants from various higher education institutions, including those both affiliated and unaffiliated with student organizations. Mediation analysis was conducted to test the proposed model. The results indicate that SDO has a significant direct effect on radical intentions (p < .001). Furthermore, SDO significantly influences radical intentions indirectly through activism as a mediator (p = .002). These findings demonstrate that SDO can foster students' radical intentions both directly and indirectly through their involvement in activism. This study contributes to the existing literature by elucidating how SDO influences students' radical tendencies through their engagement in activism.